Intelligence and Brain Efficiency: Investigating the Association between Working Memory Performance, Glutamate, and GABA - Marsman, Anouk; Mandl, René C. W.; Klomp, Dennis W. J.; Cahn, Wiepke; Kahn, René S.; Luijten, Peter R.; Hulshoff Pol, Hilleke E. (Frontiers in Psychiatry, 2017)
Intelligence is a measure of general cognitive functioning capturing a wide variety of different cognitive functions. It has been hypothesized that the brain works to minimize the resources allocated towards higher cognitive functioning. Thus, for the intelligent brain it may be that not simply more is better, but rather more efficient is better. Energy metabolism supports both inhibitory and excitatory neurotransmission processes. Indeed, in glutamatergic and GABAergic neurons, the primary energetic costs are associated with neurotransmission. We tested the hypothesis that minimizing resources through the excitation- inhibition balance encompassing GABA and glutamate may be beneficial to general cognitive functioning using 7T 1H-MRS in 23 healthy individuals (male/female=16/7, 27.7±5.3 years). We find that a higher working memory index is significantly correlated with a lower GABA to glutamate ratio in the frontal cortex and with a lower glutamate level in the occipital cortex. Thus, it seems that working memory performance is associated with the excitation-inhibition balance in the brain.